Elites and taxation: Perceptions of taxes among Córdoba businesspeople - Paulina Santa-Cruz (Íconos)
In order to analyze the configuration and transformations of tax systems in Latin America, it is essential to know how taxpayers perceive taxes. As part of the discussions on economic élites and tax systems in the region, this article proposes to investigate the tax perceptions of the local economic élite in the province of Córdoba, Argentina (2020). Using a positional sample, twenty-three interviews were conducted with Cordoban businessmen articulated in the campaign "Córdoba, acá estamos". First, it should be noted that businessmen occupy heterogeneous positions in the productive structure, but hold homogeneous perceptions regarding taxes. Then, the article recognizes a set of moral and economic questions raised by businessmen to the tax system. Moral questions denote the moral voice of the business community, while economic questions are based on neoclassical expert knowledge that circulate as common sense among the interviewees. The paper highlights those moral objections show the scope of entrepreneurial agency (Schaigorodsky 2021), as the capacity of business to say and be heard on social and political issues. And, on the other hand, economic questions express the limit of entrepreneurial agency, since the adoption of technical-economic schemes as common sense hinders the thematization of facts, experiences and subjects outside the concepts of neoclassical economics.